Effect of microbial inoculant or molasses on fermentative quality and aerobic stability of sawdust-based spent mushroom substrate. (September 2016) - Kim, J.S.; Lee, Y.H.; Kim, Y.I.; Ahmadi, F.; Oh, Y.K.; Park, J.M.; Kwak, W.S.
Highlights: Lactobacillus plantarum KU5 was identified as the best strain for SMS fermentation. L. plantarum KU5 and molasses improved fermentability and aerobic stability of SMS. Ensiling in ton-bag silos reduced aerobic stability and increased NH3 -N content. Abstract: In the first experiment, the effect of two novel Lactobacillus plantarum strains was studied on the fermentation of spent mushroom substrate (SMS) through 10 d of ensiling. Based on lactic acid production and lactic acid bacteria population, L. plantarum KU5 was identified as the best strain for fermentation with a 5-L bag silo. Spent mushroom substrate was ensiled with 0.5% (v/w) L. plantarum KU5 without or with 5% molasses. Silages treated with microbial inoculant and molasses had the lowest pH and the highest fermentative odors. In a second set of experiments similar to the above 5-L silo study, the simultaneous application of L. plantarum KU5 inoculant and molasses to 80-L silos improved fermentability and aerobic stability of SMS silages. For similar treatment using ton-bag silos, aerobic stability decreased and NH3 -N content increased dramatically. In conclusion, sawdust-based SMS for animal use was successfully ensiled with L. plantarum KU5 inoculant and molasses.